2004
DOI: 10.4049/jimmunol.172.3.1426
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Preferentially Promotes the Differentiation of CD11c+ CD11bintermediate Dendritic Cells from Bone Marrow Precursors

Abstract: Sex biases in autoimmunity and infection suggest that steroid sex hormones directly modulate immune cells. We show in this study that 17-β-estradiol (E2) promotes the differentiation of functional dendritic cells (DC) from murine bone marrow precursor cells. Remarkably, ex vivo DC differentiation was inhibited in steroid hormone-deficient medium, and was restored by addition of physiological amounts of E2, but not dihydrotestosterone. DC differentiation was inhibited by the estrogen receptor (ER) antagonists I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
182
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(198 citation statements)
references
References 65 publications
13
182
1
2
Order By: Relevance
“…This suggests that androgen might play a role in protecting male mice from the development of CIA. Estrogen has been shown to influence the immune response by influencing B cell survival and modulating dendritic cell function (25,26). We observed a higher number of B cells in female mice, even though the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 37%
“…This suggests that androgen might play a role in protecting male mice from the development of CIA. Estrogen has been shown to influence the immune response by influencing B cell survival and modulating dendritic cell function (25,26). We observed a higher number of B cells in female mice, even though the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 37%
“…We previously demonstrated that physiological amounts (0.1 nM) of 17␤-estradiol (E2) promote the GM-CSF-mediated differentiation of DC from BM progenitors in ex vivo cultures derived from either female or male mice (29). Our experiments with the ER antagonist ICI 182,780, selective ER modulators, and ER␣ Ϫ/Ϫ BM cells indicated that estrogen acts via the ER to promote DC differentiation (29,30 …”
Section: Angerhans Cells (Lc)mentioning
confidence: 99%
“…Our experiments with the ER antagonist ICI 182,780, selective ER modulators, and ER␣ Ϫ/Ϫ BM cells indicated that estrogen acts via the ER to promote DC differentiation (29,30 …”
Section: Angerhans Cells (Lc)mentioning
confidence: 99%
“…Based on competition experiments with 17-␤-estradiol (E2), it was concluded that SERM were not operating through ER because E2 was not found to counteract the inhibitory effects of SERM on DC phenotype. Our own studies have shown that the development of murine bone marrow-derived DC (BMDC) from GM-CSF-stimulated precursors in vitro was promoted by the presence of E2 in the culture medium (31). Differentiation of BMDC from E2-supplemented cultures was inhibited in the presence of a molar excess of the full ER antagonist, ICI 182,780, and tamoxifen.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%